Kepuasan kualitas produk dan pelayanan pemasaran produk teh “Gamboeng” - Muhamad Nuriman; Kralawi Sita (Jurnal Penelitian Teh dan Kina, 2018)
The competition of tea business in domestic market is increasingly fierce, inevitably demanding Research Institute for Tea and Cinchona (PPTK) as a research and profit center that produces a variety of tea products (black tea, green tea, and white tea) with the "Gamboeng" brand to maintain and increase the competitiveness and excellence of its tea products for sustainability of its tea business in the future. So, knowing about customer satisfaction on product quality and marketing services for PPTK tea products is an important aspect of the tea business strategy. This study aims to determine the level of product satisfaction and marketing services of “Gamboeng” tea. This study uses a survey method with a quantitative descriptive approach. Data collection using interview techniques with a questionnaire in score Likert scale design. Sampling was done by simple random sampling with the Slovin formula, so the total respondents are 40 with sample units are internal public or employees of PPTK. Primary data analyzed descriptively with SPSS ver.21. The results showed that the level of satisfaction with Gamboeng tea products and marketing services was high. The highest level of product satisfaction is the product attribute component, namely the taste quality, while the lowest is the place attribute, namely the availability of product sales in various places. The highest average level of satisfaction of tea marketing services is in the assurance component, namely trust, while the lowest is the reliability and responsiveness component, namely professionalism and responsiveness to complaints, requests, and consumer claims.